Dialogue in intercultural communities : from an educational point of view - Baraldi, Claudio (Dialogue studies ;, 2009)
This book explores the meanings of educational interactions which aim to promote peace and positive relationships. This analysis is based on theories of communication and active participation in education systems, in particular in intercultural settings. The book investigates the cultural presuppositions of dialogues which can empower participants' expressions in interactions through the management of discussions and conflicts. These presuppositions are observed in the use of language in participants' narratives and interactions. The book draws on the fine-grained analysis of a large corpus of.